Adaptation Study of the Mindful Eating Questiionnare (MEQ) into Turkish - Gizem KOSE; Muhittin TAYFUR; Inci BIRINCIOGLU; Aslihan DONMEZ (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Adaptation Study of the Mindful Eating Questionnare (MEQ) into Turkish Objective: In this study we aimed to define the mindful eating and discover the reliability and validity analyses of Mindful Eating Questionnare (MEQ) in Turkish sample, which has been developed to evaluate the relationship between eating behavior and mindful eating. Method: 360 volunteer university students included to our study. Participants in the survey asked to fill Turkish form of MEQ and Eating Attitude Test (EAT) completely. The study was completed with 318 participants fully filled the scales. Results: For reliability and validity of Turkish version of MEQ; internal consistency (cronbach alfa 0.733), item-total score analyses, factor analyses, parallel form correlations (As MEQ scores increase and both EAT scores and EAT score group (cutoff:30) increases) and factor correlations [As MEQ scores increase, Disinhibition (r=0.739), Emotional Eating (r=0.700), Control of Eating (r=0.594), Eating Discipline (r=0.449), Mindfullness (r=0.523), Enterferance (r=0.502) increasings are statistically significant (p [JCBPR 2016; 5(3.000): 125-134]